Aktivisme digital dan pemanfaatan media baru sebagai pendekatan pemberdayaan masyarakat atas isu lingkungan - Inda Rizky Putri; Ellya Pratiwi (Bricolage : Jurnal Magister Ilmu Komunikasi, 2022)
This research is to find out how Saling.id is a non-profit organization that focuses on environmental issues, especially in empowering the community through the use of new media for digital activism. This research is descriptive with a qualitative approach. The data collection methods used are interviews, observation, and documentation. The results show that the activism initiated by Saling.id is hybrid activism, which is a combination of connecting action and collective action. The new media is a place for digital interaction space between Saling.id and the participants or the audience. Through its digital activism, Saling.id aims to increase public awareness about environmental and waste issues and bring these issues closer to youth. The efforts made by Saling.id to achieve this goal are by utilizing new media including Instagram, website, YouTube, TikTok, and Facebook. In addition, Saling.id often adapts its content to trends in the virtual world among young people so that messages about environmental issues and waste are easier to receive. Saling.id also collaborates with various parties, including government agencies to local musicians.